Fabricating a Self-Supported Electrode for Detecting Ammonia in Water Based on Electrodepositing Platinum-Polypyrrole on Ni Foam. Issue 2 (30th January 2020) - Zhang, Liang; Wan, Junning; Li, Jiadan; Cui, Qiang; He, Dong; Zhao, Chun; Suo, Hui
Abstract : Ammonia, as a water pollutant, can result in water eutrophication, aquatic organisms poison and other environmental issues. Therefore, detection of ammonia in water is beneficial for protection of a water source. Herein, a direct electrochemical aqueous ammonia sensor was constructed based on Pt nanoparticles-polypyrrole/Ni foam (Pt-PPy/Ni foam) electrode. Electrochemical experiments demonstrated that the Pt-PPy/Ni foam electrode showed good electrocatalytic activity for the oxidation of ammonia in alkaline solution and a direct electrochemical aqueous ammonia sensor was proposed accordingly. Well-dispersed Pt nanoparticles with the size of 260 ± 20 nm were anchored on a PPy layer to further increase the performance, especially the detection limit of the sensor. The ammonia sensor presented a detection limit of 12.36 nM (Sensitivity/Noise = 3), a sensitivity of 4.19 μ A μ m −1 and a wide linear range from 0.5 μ m to 400 μ m, as well as presenting great anti-interference capability and stability. These excellent performances of the sensor could be mainly attributed to great electrocatalytic ability of Pt nanoparticles, self-supported structure and synergistic effect between PPy and Pt nanoparticles.